Pengembangan E-kamus Biologi Materi Klasifikasi Tumbuhan Dicotyledoneae Pada Kelas X SMA Negeri 4 Muaro Jambi: (Development of an E-Dictionary of Biology for Classification of Dicotyledoneae Plants in Class X SMA Negeri 4 Muaro Jambi) - Wuryan T Indriyani; Muswita Muswita; M. Erick Sanjaya (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to develop an e-dictionary as a medium for learning material classification of living things that has been feasible according to experts, and to find out the perceptions of teachers and students of class X SMA after using the developed media. Development research by referring to the 4D (Four-D) model with the stages of Define, Design, Develop and Disseminate due to time constraints, the research was only carried out until the develop stage. The product developed was validated by material experts and media experts, then assessed by a biology subject teacher for class X MIA SMA N 4 Muaro Jambi. The data used are qualitative and quantitative data, obtained from the results of the analysis of the calculation of questionnaires and interviews. Material expert validation was carried out three times with the percentage of the first stage obtained 46.87% included in the